A Geo-Located Web Services Architecture for next generation mobile networks. (19th December 2005) - Bayomock Linwa, Andre Claude; Pierre, Samuel
As many geo-located web services will be deployed in the future, the mobile clients will be interested in locating a specific application server based on requirements such as proximity, service cost per location area, bandwidth and server utilisation rate. This paper presents a middleware system named GLWSA (Geo-Located Web Services Architecture) that aims at satisfying these requirements as well as a thematic factorisation of common location functions used to get position of mobile clients. A GLWSA supports a set of GLWSMs (Geo-Located Web Services Manager) distributed over the mobile network. It defines protocols to discover and inform a Supplier Application Server (SAS) to migrate the service execution (of a specific client) to the nearest SAS based on the client's location. This architecture is suitable to assist mobile clients in the discovering geo-located web services process and to maintain the service execution closest to their location context.